Periodic lateralized epileptiform discharges can survive anesthesia and result in asymmetric drug-induced burst suppression - Edward C. Mader Jr; Louis A. Cannizzaro; Frank J. Williams; Saurabh Lalan; Piotr W. Olejniczak (MDPI AG, 2017)
Drug-induced burst suppression (DIBS) is bihemispheric and bisymmetric in adults and older children. However, asymmetric DIBS may occur if a pathological process is affecting one hemisphere only or both hemispheres disproportionately. The usual suspect is a destructive lesion; an irritative or epileptogenic lesion is usually not invoked to explain DIBS asymmetry. We report the case of a 66-year-old woman with new-onset seizures who was found to have a hemorrhagic cavernoma and periodic lateralized epileptiform discharges (PLEDs) in the right temporal region. After levetiracetam and before anesthetic antiepileptic drugs (AEDs) were administered, the electroencephalogram (EEG) showed continuous PLEDs over the right hemisphere with maximum voltage in the posterior temporal region. Focal electrographic seizures also occurred occasionally in the same location. Propofol resulted in bihemispheric, but not in bisymmetric, DIBS. Remnants or fragments of PLEDs that survived anesthesia increased the amplitude and complexity of the bursts in the right hemisphere leading to asymmetric DIBS. Phenytoin, lacosamide, ketamine, midazolam, and topiramate were administered at various times in the course of EEG monitoring, resulting in suppression of seizures but not of PLEDs. Ketamine and midazolam reduced the rate, amplitude, and complexity of PLEDs but only after producing substantial attenuation of all burst components. When all anesthetics were discontinued, the EEG reverted to the original preanesthesia pattern with continuous non-fragmented PLEDs. The fact that PLEDs can survive anesthesia and affect DIBS symmetry is a testament to the robustness of the neurodynamic processes underlying PLEDs.